Living conditions in Europe - 2018 edition (Luxembourg, 2018)
"This publication provides a picture of current living conditions in Europe, as well as the socio-economic factors affecting the everyday life of Europeans. Chapter 1 focuses on the financial dimensions of poverty and inequality. Chapter 2 examines to what extent a lack of adequate income can prevent people from affording an adequate standard of living. Chapter 3 presents statistics with regard to the quality of housing, while Chapter 4 provides information on the interactions between living conditions and labour and health status. Finally, Chapter 5 provides an analysis of social participation and social integration. The majority of the indicators presented in the publication come from the European statistics on income and living conditions (EU-SILC), with data up to 2016."